Climate policy and trade in polluting technologies - Shon Ferguson; Roweno Heijmans (Research Institute of Industrial Economics (IFN), 2023)
This study estimates the impact of carbon pricing on international trade in equipment used in the combustion of fossil fuels during the period 1995-2021. Using detailed data on bilateral trade combined with data on domestic carbon prices, we find that carbon pricing policies are associated with greater exports of this equipment. We provide a simple model of international trade in polluting technologies that can explain this outcome. Our results provide new evidence for this unexplored form of leakage due to more stringent climate policies.
Keywords: F14; F18; Q37; Q58; Q54; 330; emissions pricing; cap and trade; carbon leakage; international trade in technologies